Enantioselective Analysis of Mexiletine Using Chromatographic Techniques: A Review - Vashistha, Vinod K. (Current Analytical Chemistry, 2022)
Background: Mexiletine belongs to the β-amino-aryl-ether group of pharmaceutical and applied in the diagnosis of antiarrhythmics, allodynia, and myotonic disorders. In its chemical structure, it possesses a chiral center and practiced in the form of the racemic mixture. The production and accessibility of mexiletine have accompanied with a meaningful development in awareness of its pharmacologic actions. But in clinical arrhythmias and binding experiments on cardiac sodium channels, the (R)-enantiomer of mexiletine is more potent than the (S)-enantiomer. Also, (S)-enantiomer is further active in the diagnosis of allodynia than the (R)-enantiomer Methods: During the last two decades, chromatographic techniques such as HPLC, and GC coupled with mass spectrometry or field ionization detector have been used for the stereoselective analysis of MEX enantiomers Results: The direct enantioresolution deals with the use of chiral stationary phases (CSPs) with or no pre-derivatization which depend on a chromophoric entity in the racemates whereas the indirect HPLC process involves the use of chiral derivatization reagents (CDR) for the synthesis of diastereomeric derivatives of racemates. Different techniques have their strengths and weaknesses. Conclusion: Regulation of enantiomeric purity and estimation of particular enantiomers of drug molecules stay an essential topic for therapeutic, diagnostic, and regulatory uses and to promote a precise assessment of the hazards to human health by false enantiomers. This review aims to offer a systematic survey of the analytical methods (chromatography based) used in the enantioselective analysis of MEX developed in the last two decades (the year 2000 onwards).
Keywords: indirect separation